Non-autistic adults can recognize posed autistic facial expressions: Implications for internal representations of emotion - Lampi, AJ; Brewer, R; Bird, G; Jaswal, VK (Wiley, 2023)
Autistic people report that their emotional expressions are sometimes misunderstood by non-autistic people. One explanation for these misunderstandings could be that the two neurotypes have different internal representations of emotion: Perhaps they have different expectations about what a facial expression showing a particular emotion looks like. In three well-powered studies with non-autistic college students in the United States (total N = 632), we investigated this possibility. In Study 1, participants recognized most facial expressions posed by autistic individuals more accurately than those posed by non-autistic individuals. Study 2 showed that one reason the autistic expressions were recognized more accurately was because they were better and more intense examples of the intended expressions than the non-autistic expressions. In Study 3, we used a set of expressions created by autistic and non-autistic individuals who could see their faces as they made the expressions, which could allow them to explicitly match the expression they produced with their internal representation of that emotional expression. Here, neither autistic expressions nor non-autistic expressions were consistently recognized more accurately. In short, these findings suggest that differences in internal representations of what emotional expressions look like are unlikely to play a major role in explaining why non-autistic people sometimes misunderstand the emotions autistic people are experiencing.